Achievements of Pencak Silat Athletes: The Role of Parents and Coaches - Alang, Ashari; Jalil, Rasyidah; Kahar, Irsan; Ahmad, Ahmad (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
Pencak silat, one of the martial arts sports, is one of Indonesia's ancestral heritage which is widely spread throughout the archipelago. In the current development of pencak silat, it tends to become an achievement sports with high competition, thus encouraging athletes to improve their abilities. For sports, achievement is more directed at competition which ends with "win or lose" for the participating parties. Therefore, training is very necessary in winning an achievement. Qualitative research is collecting data in a natural setting with the intention of interpreting phenomena that can occur where the researcher is the key instrument, sampling data source is carried out purposively. The research subjects are 6 informants, parents and trainers and a sibling with a total of 2 parents and 2 trainers and 2 siblings. The result of this research, based on the explanation that the role of parents and coaches are necessary in increasing athletes; achievement, whether in the form of prayer, support, training facility and emotional support.